Kajian filem romantik korea projek tesis : pure love - Jangan, F. (University Malaysia Sarawak, UNIMAS., 2007)
The present research discovered hoe elements such as plot, narrative structure, theme, characterization and cinematic technique that has been used in Korean romantic films proficient in magnetizing audience. This research is not a sweeping statement or general conclusion made by researcher, instead, it might be useful tool as guidance and fundamental for future research.